(3eQGbj GdadGM HEeOGO GdaJGM TQM fhQ GdEjVGM hfLGI GdCQhGMs - (3GdoqToQrfoHdGdj GdeUQj, MSf Hf YeGQ Hf Ydj, (B1069 (3g`s ((3ESeGYjd GdbRGfjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj TQa NdGUI YHGOg HhQGKI NjQ YHGOg hCeOge HGdYfGjI s
(3BNQgG (B:s
(3ceG cTaJ Yf QShdc MRfg hcQHg aj gPG GdebGe jG MfGf jG efGf jG cKjQ GdeYQha hGdEMSGf jG OGFe GdfYe jG CQMe GdQGMejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 208s
(3eYLe GdeDdajf (B1 / 575s
(3EjVGM Gdecfhf (B2 / 463s
(3gOjI GdYGQajf (B1 / 292s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs